Fragile X mental retardation protein is necessary for neurotransmitter-activated protein translation at synapses - Weiler, Ivan Jeanne (National Academy of Sciences, 2004)
Fragile X mental retardation is caused by absence of the RNA-binding protein fragile X mental retardation protein (FMRP), encoded by the FMR1 gene. There is increasing evidence that FMRP regulates transport and modulates translation of some mRNAs. We studied neurotransmitter-activated synaptic protein synthesis in fmr1-knockout mice. Synaptoneurosomes from knockout mice did not manifest accelerated polyribosome assembly or protein synthesis as it occurs in wild-type mice upon stimulation of group I metabotropic glutamate receptors. Direct activation of protein kinase C did not compensate in the knockout mouse, indicating that the FMRP-dependent step is further along the signaling pathway. Visual cortices of young knockout mice exhibited a lower proportion of dendritic spine synapses containing polyribosomes than did the cortices of wild-type mice, corroborating this finding in vivo. This deficit in rapid neurotransmitter-controlled local translation of specific proteins may contribute to morphological and functional abnormalities observed in patients with fragile X syndrome.